The Synergism of Platinum-Gold Bimetallic Nanoconjugates Enhances 5-Fluorouracil Delivery In Vitro - Vareessh Maney; Moganavelli Singh (MDPI AG, 2019)
Nanoparticle application has significantly impacted the field of medicine. The need to develop novel drugs with higher therapeutic potential has stimulated the development of innovative delivery strategies to mitigate the potent side effects associated with known chemotherapeutic drugs. This paper describes the synthesis of platinum-gold bimetallic nanoparticles (PtAuBNps), their functionalisation with chitosan, and entrapment of the anticancer drug 5-fluorouracil (5-FU). All PtAuBNps and their drug nanocomposites were physico-chemically characterised, displaying desirable properties with regards to shape, size (<120 nm) and colloidal stability. 5-FU binding and loading capacities in PtAuBNps were found to be 90.17% and 22.56%, respectively. In vitro cytotoxicity profiles determined using the MTT and SRB assays reflected up to 65% cell death in the MCF-7, HepG2 and Caco-2 cell lines. These nanocomposites exhibited excellent physiochemical attributes, high specificity towards cancer cells, with a pH-sensitive drug release in a simulated acidic tumour microenvironment through zero-order release kinetics. In addition, they possessed the potential to traverse the mucosal lining facilitating oral drug administration. Overall, 5-FU encapsulation improved the bioavailability of the drug in cancer cells, with the promise of enhancing its therapeutic effect, biocompatibility and safety. These positive results highlight PtAuBNps as promising in vitro delivery systems and merits future in vivo research.